1992
DOI: 10.1021/es00034a014
|View full text |Cite
|
Sign up to set email alerts
|

Structural variations in individual carbonaceous particles from an urban aerosol

Abstract: We have used transmission electron microscopy with electron energy-loss spectroscopy (EELS) to characterize the structures of carbonaceous aerosol particles from Phoenix, AZ. The particles are <2 jum in diameter and consist of tens to hundreds of aggregated spherules. EELS reveals a range of carbon structures, from amorphous to graphitic, within aggregates. Structural variations occur among individual spherules, on a scale of approximately 0.05 fim. The energy-loss data suggest combinations of single, double, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 33 publications
2
73
0
Order By: Relevance
“…However, many studies have suggested that internally mixed LAC is usually coated with a shell of less absorbing component to form a core-shell structure rather than "well mixed". Images obtained from TEM supported that LAC particles could become coated once emitted (Katrinak et al, 1992(Katrinak et al, , 1993Martins et al, 1998). Volatility tandem DMA (differential mobility analyzer) measurements showed that the majority of particles are comprised of a non-volatile core and a volatile outer layer during heavily polluted days ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, many studies have suggested that internally mixed LAC is usually coated with a shell of less absorbing component to form a core-shell structure rather than "well mixed". Images obtained from TEM supported that LAC particles could become coated once emitted (Katrinak et al, 1992(Katrinak et al, , 1993Martins et al, 1998). Volatility tandem DMA (differential mobility analyzer) measurements showed that the majority of particles are comprised of a non-volatile core and a volatile outer layer during heavily polluted days ).…”
Section: Introductionmentioning
confidence: 92%
“…The mixing state of soot particles was observed by Katrinak et al (1992Katrinak et al ( , 1993 and Clarke et al (2004) with the TEM. A Single-particle soot photometer can be used to distinguish the coated soot particles (Schwarz et al, 2008) by measuring the incandescence and scattering at infrared wavelengths of single particles.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 114 points were analyzed by using EELS at 10 nm intervals. The π* and σ * intensities were obtained by using the same method as Katrinak et al (1992). We used intensities at 184.5, 294.5/σ *, and 402.5 eV in the EELS spectra for determining the relative abundances of S, K, and N, respectively.…”
Section: Particle Size Measurementsmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) yield detailed images of the physical structure of individual particles van Poppel et al, 2005;Hopkins et al, 2008). Electron microscopy with energy dispersive X-ray (EDX) microanalysis or electron energy loss spectroscopy (EELS) yields spatially resolved chemical composition of individual particles Katrinak et al, 1992). One general limitation of EDX is that quantitative analysis of low-Z elements (carbon, nitrogen, and oxygen) is not always possible and requires time-intensive Monte-Carlo calculations (Ro et al, 2003(Ro et al, , 2004.…”
Section: R C Moffet Et Al: Microscopic Characterization Of Carbonamentioning
confidence: 99%